Benign mixed epithelial and stromal tumor of the kidney - Michal, M; Syrucek, M (Pathology, research and practice, 1998)
We describe a distinctive benign tumor of the kidney in a 48-year-old woman, which was composed of well differentiated ducts set in the spindle cell stroma which was muscle actin, smooth muscle actin and desmin positive, and was morphologically similar to the ovarian stroma. No immature appearing epithelial renal or mesenchymal tissue was present in the tumor. Histologically, the tumor differed from the nephrogenic adenofibroma and the rare cases of adult Wilms tumors, mesoblastic nephromas and cystic nephromas.
Keywords: nádory glandulární a epitelové; nádory ledvin; buňky stromatu; Wilms Tumor; Kidney Neoplasms; Diagnosis, Differential; Stromal Cells; mezoblastický nefrom; Adenofibroma; Nephroma, Mesoblastic; nádory komplexní a smíšené; lidé; ženské pohlaví; Neoplasms, Glandular and Epithelial; Humans; diferenciální diagnóza; Neoplasms, Complex and Mixed; Wilmsův nádor; Female; lidé středního věku; adenofibrom; Middle Aged